Current landscape of nonmedical vaccination exemptions in the United States: impact of policy changes - Robert A. Bednarczyk; Adrian R. King; Ariana Lahijani; Saad B. Omer (Taylor & Francis Group, 2019)
Introduction: In the United States, high childhood vaccination coverage has reduced the morbidity and mortality due to vaccine-preventable diseases. The success of vaccination programs in achieving this high coverage is due, in part, to vaccination mandates for school entry. All states have such mandates, but there is heterogeneity across the states in the allowance of non-medical exemptions (e.g. religious or personal belief exemptions) to these mandates. Areas covered: We examine historical trends in non-medical exemption prevalence in the US, discuss recent state-level policy changes that may impact non-medical exemption prevalence, and review recent studies on the association between non-medical exemptions and infectious disease outbreaks. Expert commentary: State-level implementation of mandates, and related allowances for medical and non-medical exemptions, varies greatly across the United States. Non-medical exemption rates have increased over the last two decades, with an increased risk of disease outbreaks in clusters of children with non-medical exemptions due to differences in state laws. Recent efforts to address non-medical exemption rates range from incorporating additional administrative requirements for exemptions and disallowance of any non-medical exemptions. Continued monitoring is needed to evaluate the impact of these changes on exemption rates, to develop optimal childhood vaccination policy across the United States.